A Conceptual Framework on the Success Factors of Asnaf Entrepreneurs - Efri Syamsul, Bahri; Arman, Muhammad; Mohd Mizan, Mohammad Aslam (2021)
The success of asnaf entrepreneurs is a form of accountability of the zakat institution entity to strategic stakeholders, which in turn is accountable to Allah SWT. However, determining the success of these entrepreneurs is a problem. Therefore, this study aims to identify and describe the success factors of asnaf entrepreneurs. Charting the Field method to sort articles by topic, discussion, year, and the source was used in this study. Meanwhile, data was obtained from a literature review of various sources, including reference journals for 2016-2020. This study produces a conceptual framework regarding the success factors of asnaf entrepreneurs, namely: motivation, competency, and productive zakat. From the results, 5 aspects in the success of asnaf entrepreneurs were identified, namely, financial performance, non-financial performance, life-improvement, rich materially, and rich spiritually. Also, the success of these entrepreneurs has positively impacted the good governance of zakat and transformed them from mustahiq to munfiq and eventually muzaki. This study enriches previous limited studies on asnaf entrepreneurs and contributes to academic development, entrepreneurial asnaf, poverty alleviation, and good zakat disbursement.